University-industry cooperation in terms of textile-apparel education - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
University and industry occurred and developed independently from each other. However, during the development and progress period of societies, they involved in more intensive interaction. By being an element of science and technology dynamic relationship, university-industry cooperation is a long process with its economic, social, political, and cultural results. This takes important place in academicians', industrialists', researchers', politicians' agenda. When it's considered about science's technological and technology's scientific content; university-industry cooperation is not a choice for university and industry, it is a vital obligation. Textile-apparel sector get together with the universities at the university-industry cooperation meetings but they did not have long term cooperation. The purpose of this study is; to examine university-industry cooperation, to acquaint partners about expectations and sanctions, and to offer suggestions about institutionalization the cooperation according to views of high education institutions in Turkey which give textile-apparel education and textile-apparel industrial managers. The universe of this study are; department heads of high education institutions which give textile-apparel education at undergraduate and graduate level in Turkey, and textile-apparel industrial managers. While making the sample group the staged sampling method is used. For data collecting technique survey method is preferred. In the surveys likert scale with 5 is used. The surveys which developed to gain research data are reached to the sample group by Marmara University Survey Site and made answered via internet. The data are evaluated by using SPSS -Statistical Packages for Social Sciences. As a result of this study, according to the data gained from industrial managers' and department heads' answers, the current situation is summarized and some suggestions are offered for continues cooperation. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: University-industry cooperation; textile-apparel education; textile-apparel industry